Ergonomics Analysis of Classroom Furniture - Shofura, Rafa; Abner, Kevin; Zuraida, Rida (Jurnal Tekno, 2024)
One of the University Campus in Semarang city provides two types of class facilities: regular classes and creative classes. The first type is equipped with traditional non-adjustable chairs with desks arranged facing the front of the room, while the second types are equipped with movable whiteboard desks, adjustable wheeled chairs, and interactive whiteboards. Both types of rooms are facilitated with a whiteboard and standard projector. In the creative class, the tables and chairs are easily moved to support the learning process. For the students, to be in a sitting position in long hours in the class using the furniture that doesn't fit properly, can result in poor posture and even problems with the musculoskeletal system This study discusses the design of both classes based on anthropometric and ergonomic related to the furniture and the layout. Students’ comfort during the learning process and social interaction were captured using a questionnaire. Preferences and perceptions about the comfort of the classroom were analysis to determine opportunities for improvement that can enhance the learning environment.